2018
DOI: 10.2147/ppa.s157221
|View full text |Cite
|
Sign up to set email alerts
|

Medical and laboratory assessment for regular blood donors in Sulaimani Blood Bank, Iraq

Abstract: IntroductionIt has been suggested that blood donation reduces risks of developing cardiovascular diseases such as heart failure, atherosclerosis, and stroke. Although there are known benefits of blood donation, the inclination of people of the Kurdistan Region of Iraq to donate blood is not known. Therefore, the aim of this study was to determine demograpic and blood biochemical profiles of regular and first-time blood donors in the Sulaimani province of North Iraq.MethodsA cross-sectional study was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
2
3
2
Order By: Relevance
“…In contrast to our stud, Getta et al showed that BMI in regular donors was significantly higher than obtained in the first time donors (P < 0.001) [22]. It is possible that most people with higher BMI, advanced age and low physical activity tend to show an unfavorable plasma lipid profile that may predispose them to cardiovascular diseases.…”
Section: Anthropometric Parameter Of the Different Study Groupscontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to our stud, Getta et al showed that BMI in regular donors was significantly higher than obtained in the first time donors (P < 0.001) [22]. It is possible that most people with higher BMI, advanced age and low physical activity tend to show an unfavorable plasma lipid profile that may predispose them to cardiovascular diseases.…”
Section: Anthropometric Parameter Of the Different Study Groupscontrasting
confidence: 99%
“…Adediran et al observed that decrease in TC has been associated with repeated donations; while LDL in regular donors was reported to be lower in regular donors than in first-time donors [21]. Our study is consistent with the previous study which showed that regular blood donors had lower plasma LDL level than the first-timers [22].…”
Section: Lipid Profile Levels Of the Different Study Groupssupporting
confidence: 92%
“…In contrast to our stud, Getta et al showed that BMI in regular donors was signi icantly higher than obtained in the irst time donors (P < 0.001) [22]. It is possible that most people with higher BMI, advanced age and low physical activity tend to show an unfavorable plasma lipid pro ile that may predispose them to cardiovascular diseases.…”
Section: Anthropometric Parameter Of the Different Study Groupscontrasting
confidence: 99%
“…Adediran et al observed that decrease in TC has been associated with repeated donations; while LDL in regular donors was reported to be lower in regular donors than in irst-time donors [21]. Our study is consistent with the previous study which showed that regular blood donors had lower plasma LDL level than the irst-timers [22]. In contrast to the above reportsMasukaetal suggested that there was no difference in TC, HDL, LDL/HDL ratio and TC/HDL ratio of the participants.…”
Section: Lipid Profi Le Levels Of the Different Study Groupssupporting
confidence: 92%
“…plasma viscosity, Hct, and fibrinogen, and iron stores [5,27]. In this region, a recent study by Getta and Ahmad et al [28] investigated the purpose of blood donation and identified the main reasons for blood donations among regular donors were relieving headaches (45%), polycythemia, neck and shoulder pains, dizziness, insomnia, and sleepiness. While the reasons for donations by the first time donors were to help relatives (31%), it is evident that the benefits of blood donation outweighed its drawbacks.…”
Section: Discussionmentioning
confidence: 99%